STRENGTHENING GENERATION Z CHARACTER EDUCATION BASED ON QUR'ANIC VALUES IN THE ERA OF SOCIETY 5.0 - Sarah Dina; Sembodo Ardi Widodo (Academic Bright Collaboration, 2026)
This study aims to analyze the strengthening of Generation Z character education based on Al-Quranic values ​​in the Society 5.0 era, including the philosophical foundation, forms of internalization of values, and their relevance in facing the challenges of digital disruption and contemporary moral crises. The study uses a qualitative approach with a library research type through analysis of primary and secondary sources related to character education, Al-Quranic values, Generation Z, and Society 5.0. Data analysis techniques are carried out descriptively-analytical and interpretative to find the construction of character education from the perspective of Al-Quran. The results show that Al-Quran-based character education is not only oriented towards the formation of normative morals, but also emphasizes the transformation of spiritual awareness, self-control, and social responsibility. Core values ​​such as monotheism, trustworthiness, discipline, honesty, moderation, empathy, and responsibility are the foundation in building the character of Generation Z amidst the increasingly complex development of digital technology. Strengthening Qur'anic character is implemented through the integration of tazkiyatun nafs, morals, and adab with a pedagogical approach in the form of role models, Qur'anic stories (qashash), educational dialogue, habituation, and targhib and tarhib. In addition, the example of the Prophet Muhammad SAW is a model of character education practices that are relevant in forming an adaptive generation but still based on spiritual values ​​and social ethics. This study recommends strengthening Qur'an-based character education in an integrative manner in the educational environment, family, and society as an effort to form a Generation Z who is faithful, has integrity, and is civilized in the era of Society 5.0.